BENTUK-BENTUK KOMPENSASI FINANSIAL - Ahmad Fatih Ubaidillah; Dewa Aray Dwiyanto; Dwi Yulfitasari (Dar El-Falah, 2024)
Compensation is an award or remuneration provided by the company to itsemployees in the form of money, direct and indirect goods as compensationbecause the employee has contributed his energy and thoughts for theprogress of the company in order to achieve the goals set. Compensationfunctions: (a) Efficient allocation of human resources, (b) More efficientand effective use of human resources, (c) Encouraging stability andeconomic growth. Compensation objectives: (a) Appreciate workperformance, (b) Cooperation bonds, (c) Job satisfaction, (d) ensurefairness, (e) retain good and quality employees, (f) control costs, (g) complywith regulations , (h) motivation and discipline. Forms of financialcompensation: (a) salary, namely remuneration that is paid periodically topermanent employees and has a definite guarantee (b) benefits, namelycompensation given by the company to its employees because they areconsidered to have participated well in achieving company goals, and (c) incentives, namely compensation given to certain employees because of thesuccess of their achievements